Study guides

☆☆

Q: How do you solve -7x plus 6 plus 7x-2?

Write your answer...

Submit

Still have questions?

Related questions

x3 - 7x2 + 6x =x (x2 - 7x + 6) =x (x - 6) (x - 1)

7x2-19x-6 7*6=427x2-2x+21x-6[7xx 2x] [3*7x 2*3]x(7x-2)+3(7x-2)Answer: (7x-2)(x+3)

(7x + 2)(x - 3)

(x - 3)(7x + 2)

(7x + 6)(x - 2)

Try to factor the left side and set each of the linear expressions equal to zero. 7x^2 +8x -12= 0 (7X-6)(X+2)=0 7X-6=0 X=6/7 X+2=0 X=-2

7x+6 = -3x-24 7x+3x = -24-6 10x = -30 x = -3

7x-4=x+2 7x=x+2+4 7x=x+6 7x-x=6 6x=6 X=1

4x+9 = 7x+3 4x-7x = 3-9 -3x = -6 x = 2

6 = 7x + x First, add 7x and x.6 = 8xNow, divide both sides by 8.6/8 = xSimplify the answer.3/4 = x.

-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3

x2 + 7x + 6 = (x + 6) (x + 1)

9x+6 = 7x+18 9x-7x = 18-6 2x = 12 x = 6

x3 - 7x2 + 6x = x(x2 - 7x + 6) = x(x2 - x - 6x + 6) = x[x(x - 1) - 6(x - 1)] = x2(x - 1) - 6x(x - 1) = (x2 - 6x)(x - 1)

x^2 +7x+6 = (x+1)(x+6) when factored

7x2+49x-42 = 7(x2+7x-6)

The answer to the math problem of 5x plus 7x-4x 6 is -12.

7x-3=39 7x=42 x=6

The correct answer is one of: A: (7x + 5)*(7x + 6) = 49x2 + 77x + 30 B: (7x + 5)*7x + 6 = 49x2 + 35x + 6 C: 7x + 5*7x + 6 = 42x + 6 Since there are no brackets in the question, the correct answer is C but I suspect there should be brackets but this site does not allow them.

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

7x+y=6

7x + 6

if the equation was 7x = 42. The answer would be x = 6

49x^2 + 77x + 30 Improved answer: 7x+57x+6 When simplified: = 64x+6

Do you mean: 5x + 9 - 7x + 6 = x - 18 If so, you can solve this question at this manner: -2x + 15 = x - 18 3x = -3 x = -1